Penerjemahan Biografi Tjilik Riwut di Museum Balanga Palangka Raya - Faila Nafsha Andiny; Sifa Hayati; Muhammad Raffy; Yasin Ali Rogas; Zhira Ayu Annisa; Akhmad Fauzan (FKIP Universitas Mataram, 2026)
This community service activity aims to provide English-language information at the Balanga Museum, especially at the Tjilik Riwut Museum, in Palangka Raya City, Central Kalimantan Province. The translation of documents in the form of Tjilik Riwut’s biography was carried out by a team consisting of one lecturer and five students from the English Language Education Study Program at Universitas Palangka Raya through service learning method. The translated documents contain information about Tjilik Riwut’s biography, military career, government career, and trivia. These texts were translated from Indonesian into English with the attention to accuracy of meaning and acceptability in the target language. The translation results submitted to the Head of the Balanga Museum are in the form of printed text and a standing banner containing a summary of Tjilik Riwut’s biography and a QR code that will direct to an online folder containing the full text.